A formação de pedagogos para o uso crítico das tecnologias no município de Belém do Pará - COSTA, Débora Souto da (Universidade Federal do Pará, 2019)
This study aims to investigate if the curricula of the pedagogy courses, from three public higher education institutions of the city of Belém, allow teacher education focused on the critical use of Information and Communication Technologies. The contributions of Paulo Freire, Miguel Arroyo, Vani Kensky, Pierre Levy, and other authors were used as theoretical contributions. We chose a qualitative, descriptive and documentary methodology. To analyze the data, we used Content Analysis. The results revealed that there are indications for the possibility of critical formation from the use of information and communication technologies, albeit timidly, among the researched curricula. However, it is concluded that there is a need to rethink ways to enable this formation in an effective and critical way.